A MacIntyrean account of chronic moral injury: Assessing the implications of bad management and marginalized practices at work - Abadal, Lily M.; Potts, Garrett W. (Frontiers in Sociology, 2022)
In this article, we engage with a theory of management advanced by MacIntyrean scholars of business ethics and organization studies to develop an account of “chronic moral injury” in the workplace. In contrast to what we call “acute moral injury,” which focuses on grave, traumatic events, chronic moral injury results from poor institutional form—when an individual desiring excellence must function within a vicious institution that impedes the acquisition of virtues and marginalizes practices. In other words, chronic moral injury occurs when practitioners who pursue excellence in their practice work within corrupt or malformed organizations. To demonstrate this point, we recount the events associated with the rise and fall of the biotech company, Theranos. This case study advances an empirical contribution to MacIntyrean studies by demonstrating how chronic moral injury can happen under such conditions and what the negative consequences may entail for workers.